Antiplatelet treatments: recent evidence from randomized controlled trials. (July 2017) - Vogel, Birgit; Baber, Usman
Abstract : Purpose of review: To provide an overview of selected randomized studies reported over the last 2 years evaluating antiplatelet therapies in patients with either acute or stable manifestations of atherosclerosis. Recent findings: From large outcome trials included evidence for reduced risk of ischemic events associated with use of ticagrelor and aspirin versus aspirin alone, albeit with an increased bleeding risk in patients with stable coronary artery disease and history of myocardial infarction. No benefit regarding ischemic outcomes could be demonstrated for ticagrelor monotherapy compared with aspirin or clopidogrel in patients with stroke or peripheral vascular disease, respectively. Results from pharmacokinetic/pharmacodynamic studies suggest that switching from prasugrel to ticagrelor is safe, regardless of the use of a loading dose, and that loading with prasugrel or ticagrelor compared with clopidogrel leads to more prompt and potent platelet inhibition in patients undergoing ad hoc percoutaneous coronary intervention. No evidence could be demonstrated for the prognostic value of routine platelet function monitoring to adjust antiplatelet therapy. Summary: Large outcome trials demonstrated various effects of antithrombotic strategies including ticagrelor on clinical outcomes across patient populations. Pharmacokinetic/pharmacodynamic studies confirmed a more prompt and potent platelet inhibition after loading with the new P2Y12 inhibitors versus clopidogrel, and suggested the safety of switching from prasugrel to ticagrelor.